2009
DOI: 10.5664/jcsm.27490
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, Tiredness, and Lack of Energy Improve with Treatment for OSA

Abstract: Scientific inveStigatiOnSObjectives: Many patients with obstructive sleep apnea complain of fatigue, tiredness, or lack of energy in addition to sleepiness, or instead of sleepiness. We explored whether self-defined fatigue, tiredness, and lack of energy improve, like sleepiness, after treatment with positive airway pressure (PAP). Methods: We conducted a prospective survey of adults referred to a University-based sleep disorders center and confirmed to have obstructive sleep apnea on polysomnography. Surveys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Gender differences are also not consistently controlled for, which may contribute to varying degrees of fatigue in OSA (Chotinaiwattarakul, O'brien, Fan, & Chervin, 2009;Lee et al, 2014;Quintana-Gallego et al, 2004) and HF patients (Ekman & Ehrenberg, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Gender differences are also not consistently controlled for, which may contribute to varying degrees of fatigue in OSA (Chotinaiwattarakul, O'brien, Fan, & Chervin, 2009;Lee et al, 2014;Quintana-Gallego et al, 2004) and HF patients (Ekman & Ehrenberg, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment: Treatment of sleep-related breathing disorders in MS is not different from treatments used for the non-MS patients including lifestyle modifications such as weight loss, smoking cessation, alcohol reduction and respiratory support using the continue positive airway pressure (CPAP) [59] or bilevel positive airway pressure (BiPAP) [60]. While CPAP generally delivers a single pressure, BiPAP delivers an inhale pressure and an exhale pressure.…”
Section: Sleep Related Breathing Disordersmentioning
confidence: 99%
“…Alternatively, various dental appliances have been used in order to maintain an open air way but occasionally surgical approaches are recommended. Treatment of sleep-related breathing disorders in MS could led to significant improvement of fatigue and tiredness [59].…”
Section: Sleep Related Breathing Disordersmentioning
confidence: 99%
“…Once patients have OSAHS, they complain of intolerance to exercise and both muscle and general fatigue (Aguillard et al, 1998;Chotinaiwattarakul et al, 2009;Vanuxem et al, 1997). It has been shown that OSAHS is associated with selfreported lack of exercise (Peppard and Young, 2004).…”
Section: Introductionmentioning
confidence: 99%